Charge parity violation in the minimal supersymmetric standard model (MSSM) and some new interactions - Ha, Huy Bang (H. : ĐHQGHN, 2017)
We present the appearance of some new interaction in the MSSM with CP violation. We give analytic formulae and perform an evaluation of the effects of these new interactions on some processes concerning the productions and decays of squarks. We find that these effects are topically of —3.5% to + 3 % depending on each process.